2016
DOI: 10.5812/ircmj.28941
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lemon balm (Melissa officinalis L.) Alone and in Combination With Nepeta menthoides on the Menstrual Bleeding in Students With Premenstrual Syndrome: A Randomized Controlled Trial

Abstract: Background: An increased amount of menstrual bleeding in women causes anemia and decreased quality of life. Objectives: The present study aimed to determine the effects of lemon balm alone and in combination with Nepeta menthoides on menstrual bleeding in students with premenstrual syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…On the other hand, the biochemical analysis showed that the combination of ineffective doses significantly increased CAT activity in the brain. However, Mirghafourvand, Malakouti, Mohammad, Farshbaf, and Ghanbari (2016) reported that there was no statistically significant difference between extracts alone and their combinations in their clinical trial. It seems that further animal and clinical studies are needed to demonstrate that the combination of two plants has no difference with their single‐use.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the biochemical analysis showed that the combination of ineffective doses significantly increased CAT activity in the brain. However, Mirghafourvand, Malakouti, Mohammad, Farshbaf, and Ghanbari (2016) reported that there was no statistically significant difference between extracts alone and their combinations in their clinical trial. It seems that further animal and clinical studies are needed to demonstrate that the combination of two plants has no difference with their single‐use.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have assessed the effects of some herbal drugs on menstrual bleeding (20,21). However, according to a systematic review, further well-designed trials are recommended to investigate the safety and efficacy of herbs in the treatment of women with menorrhagia (22).…”
Section: Introductionmentioning
confidence: 99%